Each number in the sequence is dubbed a term (or periodically "element" or "member"), review Sequences and series for an ext details.

You are watching: What is the common difference in the following arithmetic sequence?

## Arithmetic Sequence

In one Arithmetic sequence the difference in between one term and the next is a constant.

In other words, we just include the same value each time ... Infinitely.

This sequence has a distinction of 3 between each number. The sample is ongoing by adding 3 to the last number every time, favor this: In General we might write one arithmetic sequence favor this:

a, a+d, a+2d, a+3d, ...

where:

a is the an initial term, and d is the difference in between the state (called the "common difference")

Has:

a = 1 (the an initial term) d = 3 (the "common difference" between terms)

And we get:

a, a+d, a+2d, a+3d, ...

1, 1+3, 1+2×3, 1+3×3, ...

1, 4, 7, 10, ...

### Rule

We deserve to write an Arithmetic Sequence as a rule:

xn = a + d(n−1)

(We usage "n−1" since d is not provided in the 1st term).

This sequence has actually a distinction of 5 between each number. The values of a and d are:

a = 3 (the first term) d = 5 (the "common difference")

Using the Arithmetic sequence rule:

xn = a + d(n−1)

= 3 + 5(n−1)

= 3 + 5n − 5

= 5n − 2

So the 9th term is:

x9 = 5×9 − 2 = 43

Is the right? inspect for yourself!

## Advanced Topic: Summing one Arithmetic Series

To amount up the terms of this arithmetic sequence:

a + (a+d) + (a+2d) + (a+3d) + ...

use this formula:

What is that funny symbol? that is dubbed Sigma Notation (called Sigma) way "sum up"

And below and above it are presented the beginning and finishing values: It states "Sum up n wherein n goes from 1 come 4. Answer=10

### Example: add up the first 10 terms of the arithmetic sequence:

1, 4, 7, 10, 13, ...

The values of a, d and n are:

a = 1 (the very first term) d = 3 (the "common difference" between terms) n = 10 (how many terms to include up)

So:

Becomes: = 5(2+9·3) = 5(29) = 145

Check: why don"t you add up the terms yourself, and see if it involves 145

## Footnote: Why go the Formula Work?

Let"s watch why the formula works, because we obtain to usage an exciting "trick" i beg your pardon is precious knowing.

First, us will contact the whole sum "S":

Now include those two, ax by term:

 S = a + (a+d) + ... + (a + (n-2)d) + (a + (n-1)d) S = (a + (n-1)d) + (a + (n-2)d) + ... + (a + d) + a 2S = (2a + (n-1)d) + (2a + (n-1)d) + ...See more: How To Say Happy Holidays In Spanish For Your Tarjetas De Navidad + (2a + (n-1)d) + (2a + (n-1)d)

Each hatchet is the same! And there are "n" that them so ...